Review on Software Testing Metrics (International Journal of Engineering and Computer Science, 2014)
Metrics are defined as standards of measurement. Test metrics provides the visibility into the readiness of the product, and gives clear measurement of the quality and completeness of the product. Metrics allow for deeper understanding of the performance of the application and its behavior. Metrics help organization to obtain the information it needs to continue to improve its productivity, reduce errors and improve acceptance of processes, products and services and achieve the desired goal. This paper focuses on various types of testing metrics, and introduces the most commonly used software metrics and projected their use in constructing models of the software development process.